การพัฒนารูปแบบการเสริมสร้างพลังอำนาจชุมชนเพื่อเสริมสร้างจิตสำนึก ของความเป็นพลเมืองดีในวิถีชีวิตประชาธิปไตย - คงเจริญ มิ่งขวัญ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยครั้งนี้เป็นกรณีศึกษาชุมชนตัวอย่างที่ได้รับรางวัลด้านความเป็นประชาธิปไตยในพื้นที่ต่าง ๆ เพื่อวิเคราะห์องค์ประกอบของปัจจัยสนับสนุนและบริบทที่ส่งเสริมการเสริมสร้างจิตสำนึกของความเป็นพลเมืองดีในวิถีชีวิตประชาธิปไตยของชุมชนตัวอย่าง โดยใช้แนวทางการวิจัยเชิงคุณภาพ ที่เน้นการหาความเข้าใจในรายละเอียดของกรณีศึกษาด้วยวิธีการสัมภาษณ์แบบเจาะลึกของการเสริมสร้างพลังอำนาจชุมชน เพื่อสร้างจิตสำนึกของความเป็นพลเมืองดีในวิถีชีวิตประชาธิปไตย ผลการวิจัยพบว่ารูปแบบการเสริมสร้างพลังอำนาจชุมชนเพื่อเสริมสร้างจิตสำนึกของความเป็นพลเมืองดีในวิถีชีวิตประชาธิปไตยของชุมชนโดยมีองค์ประกอบสำคัญ คือ 1) ทักษะบุคคล ได้แก่ ความตระหนักรู้และเห็นคุณค่าในตนเอง และการรับรู้ข่าวสาร 2) การมีส่วนร่วมชุมชนและสังคม ได้แก่ ความรับผิดชอบต่อตนเอง/สังคม ความสามารถร่วมทำงานกับผู้อื่นได้ ท่ามกลางความหลากหลายทางวัฒนธรรม การมีวิถีชีวิตที่ไม่ส่งผลร้ายต่อชุมชน/สิ่งแวดล้อม และความสามารถแก้ปัญหาด้วยสันติวิธี และ 3) ความรู้ความเข้าใจเกี่ยวกับประชาธิปไตย ได้แก่ การมีความรู้ ความเข้าใจ และประยุกต์ใช้การเมืองการปกครอง ที่สามารถถ่ายทอด วิพากษ์วิจารณ์และตัดสินนโยบาย ผลงาน และกรณีต่างๆ ได้อย่างถูกต้องและเหมาะสม มีความสามารถนำหลักการประชาธิปไตยไปใช้ในการดำเนินชีวิตและการทำงานได้อย่างถูกต้องและเหมาะสม และความกระตือรือร้นในการเป็นสังคมแบบประชาสังคม (civil society) คำสำคัญ : การเสริมสร้างพลังอำนาจชุมชน, การเสริมสร้างจิตสำนึกของความเป็นพลเมืองดี ในวิถีชีวิตประชาธิปไตย ABSTRACT This research was a case study of various community areas that received the award from implementing the democratic principles in their areas. The purpose of the case study was to analyze the key elements of the factors that support as well as the context that supplement in strengthening the consciousness of good citizenship in the democratic way of life. The research used the mixed methodology composed of 1) quantitative research methodology in analyzing the key elements that supplement in strengthening the consciousness of good citizenship in a democratic way of life and 2) qualitative research methodology to emphasis is on understanding the details of case studies. By in-depth interviews with community empowerment to strengthen the consciousness of good citizenship in the democratic way of life. The results of this research were : The community empowerment model to strengthen the consciousness of good citizenship in the democratic way of life has the following components:1) In the aspect of personal skills include awareness and self-esteem, Recognition of information. 2) In the aspect of community and social participation include has self and social responsibility, able to work with others among diversities cultural between each communities, a lifestyle has no adverse effect to the community or environment and able to solve problems by peaceful means. 3) In the aspect of knowledge and understanding democracy include has knowledge, understanding , apply and relay the knowledge on politics, criticize and judge the policies and work in various situation correctly and appropriately, able to apply the principles of democracy in the daily life correctly and appropriately and enthusiasm for being a member of the civil society Keywords : community empowerment, strengthen the consciousness of good citizenship in the democratic way of life